POMPP Score and Boey Score: To Predict Mortality in Peptic Ulcer Perforation - Khadka, Digbijay Bikram; Bharti, Shiv Vansh; Khadka, Sagun Jung; Sharma, Anup (Journal of Nepalgunj Medical College, 2022)
Introduction: Peptic ulcer is an insult to the mucosa of the upper digestive tract. Helicobacter pylori infection, long term use of non-steroidal anti-inflammatory drugs or steroids, excessive alcohol ingestion and smoking are common etiological factors. A number of scoring systems for prediction of outcomes in perforated peptic ulcer patients have been developed such as Predictive score of mortality in perforated peptic ulcer score and Boey score. Aims: To evaluate Predictive score of mortality in perforated peptic ulcer score and Boey Score in predicting accuracy of mortality in patients with peptic ulcer perforation. Methods: A hospital based study was conducted from June 2021 to May 2022 in the department of Surgery, Nepalgunj Medical College, Kohalpur. The Predictive score of mortality in perforated peptic ulcer and Boey score were recorded after history taking, physical examination, basic pre-operative investigations and radiological imaging. The patients were classified into high risk and low risk categories based on scores and followed up to predict the mortality within 30 days post operatively. Results: 80 patients were included in the study. 53 were male and 27 female. Peptic ulcer perforation was seen more in age groups of 45 to 60 years. In Boey score 8 patients out of 27 high risk patients died whereas in Predictive score of mortality in perforated peptic ulcer score 8 patients died out of 12 high risk patients. When compared, predictive score of mortality in perforated peptic ulcer was found to be more accurate than Boey score (p-<0.05) score. Conclusion: Predictive score of mortality in perforated peptic ulcer is easy to use and more accurate in predicting mortality in peptic ulcer perforation than Boey score.